2022
DOI: 10.7554/elife.72290
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of behavioral and electrophysiological phenotypes in a Pitt-Hopkins syndrome mouse model by genetic restoration of Tcf4 expression

Abstract: Pitt-Hopkins syndrome (PTHS) is a neurodevelopmental disorder caused by monoallelic mutation or deletion in the transcription factor 4 (TCF4) gene. Individuals with PTHS typically present in the first year of life with developmental delay and exhibit intellectual disability, lack of speech, and motor incoordination. There are no effective treatments available for PTHS, but the root cause of the disorder, TCF4 haploinsufficiency, suggests that it could be treated by normalizing TCF4 gene expression. Here, we pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This suggests a transcriptional mechanism through which FOXP1 directly regulates K Leak and thereby intrinsic excitability. To our knowledge, this is one of the very few clear and reproducible demonstrations of a transcriptional mechanism regulating electrophysiological function in neurons ( 24 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This suggests a transcriptional mechanism through which FOXP1 directly regulates K Leak and thereby intrinsic excitability. To our knowledge, this is one of the very few clear and reproducible demonstrations of a transcriptional mechanism regulating electrophysiological function in neurons ( 24 ).…”
Section: Discussionmentioning
confidence: 82%
“…The extent and transcriptional mechanisms by which postnatal reinstatement of a transcription factor (after its absence during earlier developmental stages) can restore proper neuronal physiology are largely unexplored. A recent study has reported a rescue of electroencephalogram phenotype, behavior characteristics, and a few genes with postnatal reinstatement of Tcf4 ( 24 ). However, to our knowledge, no study has used a large-scale, unbiased approach in vivo to determine the extent of expression reversal and assess this at a cell type–specific level more rigorously.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also possible that the longer TCF4 isoforms have specific functions which cannot be compensated by other TCF4 isoforms, and mutations affecting only a subset of TCF4 isoforms result in less severe effects than seen for mutations affecting all the isoforms. Recently, it has been shown that postnatal normalization of TCF4 expression to wild type levels can rescue the phenotype of TCF4 heterozygous knockout mice ( Kim et al, 2022 ). In addition, studies of Daughterless, the orthologue of TCF4 in the fruit fly, have shown that it is possible to partially rescue the severe embryonic neuronal phenotype of Daughterless null mutation by overexpressing either human TCF4-A or TCF4-B ( Tamberg et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The extent and transcriptional mechanisms by which postnatal reinstatement of a transcription factor (after its absence during earlier developmental stages) can restore proper neuronal physiology is largely unexplored. A recent study has reported a rescue of EEG phenotype, behavior characteristics, and a few genes with postnatal reinstatement of Tcf4 24 . However, to our knowledge, no study has used a large-scale, unbiased approach in vivo to more rigorously determine the extent of expression reversal and assess this at a cell-type-specific level.…”
Section: Introductionmentioning
confidence: 98%